A review of angle-resolved photoemission spectroscopy study on topological magnetic material family of MnBi2Te4. (1st December 2022) - Jiang, Zhicheng; Liu, Jiayu; Liu, Zhengtai; Shen, Dawei
Abstract: The MnBi2 Te4 family compounds have drawn enormous attention in recent years due to their potential to realize the high-temperature quantum anomalous Hall effect. As one of the most direct techniques to probe electronic structure, angle-resolved photoemission spectroscopy (ARPES) has been widely applied to investigate the interplay between the magnetism and non-trivial topological band structure of MnBi2 Te4 family materials. Here, we briefly review some of latest progress in ARPES study of MnBi2 Te 4 ⋅ (Bi2 Te3 ) ( n = 0, 1, 2, 3) and analogous MnSb2 Te 4 ⋅ (Sb2 Te3 )2 ( n = 1, 2) series of materials. Aside from the direct observation of the non-trivial topological band structure, ARPES results reveal that their surface band gap can be well modulated by both temperature and Bi2 Te3 interpolation. In addition, although ARPES results of the topological surface states are still under hot debate, the extensive experimental results have provided an opportunity to shed light on the complex interactions in intrinsic magnetic topological insulator.